Genetic epidemiology of multiple sclerosis. - Ebers, G (1996)
Multiple sclerosis appears to be a complex trait determined by genes and environmental factors. This hypothesis is increasingly supported by genetic epidemiological studies of large populations. Well ascertained studies of adoptees and half siblings indicate that familial aggregation is genetic. These results have important implications for the nature of environmental factors influencing susceptibility to multiple sclerosis. These appear to act at a population level and probably exert an influence on risk that matches or exceeds that from any single genetic locus. The identification of susceptibility genes in multiple sclerosis will be difficult.